2008
DOI: 10.3346/jkms.2008.23.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Microvascular Complications in Type 1 Diabetes Mellitus

Abstract: We examined whether alterations in vascular endothelial function and early structural changes in atherosclerosis are associated with microvascular complications in patients with type 1 diabetes mellitus (DM). Flow-mediated dilation (FMD) of the brachial artery and carotid intima-media thickness (IMT) measurement were performed in 70 young adults (aged 19 to 35 yr), 48 with type 1 DM, and 22 normal controls. Patients with diabetes had a lower peak FMD response (7.8±3.9 vs. 11.1±1.9%, p<0.001) and increased IMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
2
24
1
3
Order By: Relevance
“…In the study of Jin and cols., forty-eight patients with T1DM and twenty two healthy individuals were compared in regard to FMD and intima carotid thickness. FMD was found significantly lower in diabetics, supporting our results (22). Lekakis and cols.…”
Section: Biochemical and Clinic Markers Of Ed In T1dmsupporting
confidence: 82%
“…In the study of Jin and cols., forty-eight patients with T1DM and twenty two healthy individuals were compared in regard to FMD and intima carotid thickness. FMD was found significantly lower in diabetics, supporting our results (22). Lekakis and cols.…”
Section: Biochemical and Clinic Markers Of Ed In T1dmsupporting
confidence: 82%
“…There are some studies, not only in adults but also in children, which have previously demonstrated endothelial dysfunction using FMD evaluation with lower percentages of dilatation in T1D subjects in comparison with controls. [19][20][21][22][23][24] In addition, our paper is not the first to demonstrate a higher mean cIMT in subjects with T1D compared with a control group. 25,26 In a very recent paper, Sibal et al 27 showed impaired endothelial function (45% reduced) and increased cIMT in young people with T1D without macrovascular disease or microalbuminuria, but including 62% of subjects with retinopathy, 24% of smokers and a moderately poor average metabolic control (average HbA 1c of 8.5%).…”
Section: Discussioncontrasting
confidence: 63%
“…Low percentage of FMD was also found in patients with rheumatoid arthritis because 62 of chronic inflammation (17-18). Jin et al (19) found that FMD percentages were lower in patients with diabetes mellitus (DM) than in the control group.…”
Section: Discussionmentioning
confidence: 99%